THE DEVASTATED NATURE OF INTEREST BASED DEBT FOR DEVELOPMENT, HUMANITY AND COUNTRIES - Ghutai, Gul (Online Journal of Islamic Management and Finance (OJIMF), 2021)
Interest based debt acquired by countries for their developmental concerns through foreign funding agencies has harmed the residents of those nations. Humans are considered as commodity for the ones having power and affluence thus, having greatest concentration of wealth which is accumulated through distribution of interest-based debts. The study is conducted to analyze the devastated effect of interest-based debt obtained for developmental concerns upon humanity and countries particularly Pakistan. The question arises to what extent interest-based debt acquired for developmental purposes affected Country’s sovereignty. This study applies Qualitative research methodology in pursual of building a conceptual framework by incorporating inductive paradigm. Interest based debt acts as a curse for nation’s economic-social prosperity, political stability, and spiritual values. The study suggests that interest-based debt as phenomena helps in accumulation of national and global wealth in fewer hands. It is in the best interest of the world to be aware of corporate greed and self-interest strategies in the veil of distributing interest-based loans for developmental concerns which is a debt trap and can be avoided by enforcing interest free economic policies in their respective territories to promote socio-economic wellbeing of the masses generally and particularly in Pakistan.